Variation analysis of S1 gene of avian infectious bronchitis virus epidemicstrains isolated from chicken flocks in Henan Province - XU Xue; ZHAO Jun; WANG Chuan-qing; WANG Ze-lin; YANG Xia; ZHOU Xin; DILIBAIER Amuti (浙江大学学报. 农业与生命科学版)
Seven isolates of infectious bronchitis virus (IBV) were obtained and identified from clinical infected chicken flocks in Henan Province by using the techniques of chicken embryo inoculation, reverse transcription polymerase chain reaction (RT-PCR) and tracheal organ culture (TOC). Spike protein gene of 7 isolates and vaccine strain H120 was amplified by RT-PCR and sequenced. The result showed that the sizes of the whole length for S1 gene of 8 IBV strains were divided into four groups: 1 632, 1 620, 1 617 and 1 611 bp, respectively. There were multisite mutations among these sequences in addition to type-specific insertion and deletion. The analysis of deduced amino acid sequences showed that sequential patterns of S protein cleavage sites of 8 IBV strains fell into three categories: HRRRR, RRFRR and RRSRR. Homology and phylogenetic analysis showed that Jin-13 isolate was respiratory-type of IBV, and YI isolate was ArkDPI-type, and HN/SG isolate had a distant relationship to other domestic nephropathogenic-type isolates else, and HN/HL, XP/1/09, XP/3 and WZL isolates had a close relationship to Shandong nephropathogenic-type isolates but had a distant relationship to HN99 isolate. All results above indicate that there are different IBV epidemic isolates in Henan Province, and certain mutations at the molecular level have occurred in S1 gene.